Electroencephalogram Source Connectivity in the Prediction of Electroconvulsive Therapy Outcome in Major Depressive Disorder. (January 2020) - Kirsten, Alexandra; Seifritz, Erich; Olbrich, Sebastian
Objectives. Major depressive disorder (MDD) is a common and potentially lethal disorder affecting up to 14% of all persons worldwide. However, one-third to thwo-thirds of patients are nonresponders to first-line therapy. Even the electroconvulsive therapy (ECT) as the option of choice in therapy-resistant MDD still shows a high proportion of nonresponders. In case of a predicted nonresponse to ECT, for example, by means of electrophysiological electroencephalogram (EEG) parameters, other therapies of MDD (eg, augmentation, polypharmacy etc) could be chosen. Methods . In this study, we retrospectively analyzed 2-minute resting state EEGs from patients with MDD who underwent ECT (6-12 sessions with 3 sessions per week) between 2006 and 2015 at the University Hospital of Zurich. Following several lines of evidence, we hypothesized altered linear EEG connectivity within the alpha band being predictive for treatment outcome. We used a network-based statistics (NBS) approach to compare connectivity measures between responders and nonresponders. Source estimates and connectivity measures were mapped using low-resolution brain tomography (LORETA). As the main outcome parameter served the retrospectively assessed efficacy index (CGI-E) from the Clinical Global Impression (CGI) rating scale. Results . Responders in comparison with non-responders showed a significant lower linear lagged connectivity in widespread cortical areas within the EEG alpha 2 band. Additionally, there were strong correlations between CGI ratings and connectivity strength mainly within frontal cortices. Conclusions . Pretreatment EEG-connectivity within the alpha 2 band has a predictive value for the efficacy of ECT treatment.